Analysis and Evaluation of Land Suitability in Kupang City, Indonesia for Sustainable Settlement Development - Rakuasa, Heinrich (Institute Of Advanced Knowledge and Science, 2025)
Kupang City, as the capital of Nusa Tenggara Timur Province, faces significant challenges in land management and settlement development due to rapid population growth and urbanization. This study aims to analyze and evaluate land suitability for sustainable settlement development, considering relevant environmental factors. The method used is Spatial Multi-Criteria Analysis (SMCA), which integrates geospatial data from the Digital Elevation Model (DEM), including slope, road networks, rivers, economic activity centers, and coastlines. The analysis results indicate that out of the total area analyzed, 7,227.04 hectares have high suitability, 4,341.12 hectares have moderate suitability, and 3,967.85 hectares have low suitability. Areas with high suitability are generally located near roads, economic activity centers, have lower slope gradients, and are far from rivers and coastlines, making them ideal for infrastructure development. The discussion emphasizes the importance of spatial and participatory-based spatial planning, as well as the need for monitoring low-suitability areas to prevent disaster risks. In conclusion, this study provides policy recommendations for more sustainable settlement development in Kupang City, integrating land suitability analysis and involving the community in the planning process, thereby creating